PSYCHOLOGICAL FOUNDATIONS OF SOCIAL ADAPTATION OF STUDENTS WITH DISABILITIES - Chingiz Qakhramonovich Ochilov (Journals Park Publishing, 2023)
This article is one of the current problems in which the psychological foundations of social adaptation of students with disabilities, the need to conduct developmental education with anomalous children, methods of correction, compensation and ways to implement them are studied.
Keywords: Special pedagogy, correction, compensation, integrative, inclusive, inclusive education for abnormal children, differential education, career guidance.